2017
DOI: 10.18632/oncotarget.23055
|View full text |Cite
|
Sign up to set email alerts
|

CHAC1 degradation of glutathione enhances cystine-starvation-induced necroptosis and ferroptosis in human triple negative breast cancer cells via the GCN2-eIF2α-ATF4 pathway

Abstract: Cancer cells exhibit an abnormal amino acid metabolism and a dependence on specific amino acids, which might provide potential targets for treating cancer patients. In this study, we demonstrated that human triple negative breast cancer (TNBC) cells were highly susceptible to cystine starvation. We found that necrostatin-1 (Nec-1, a RIP1 inhibitor), necrosulfonamide (an MLKL inhibitor), deferoxamine (an ion chelator), ferrostatin-1 (a ferroptosis inhibitor) and RIP1 knockdown can prevent cystine-starvation-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
163
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(187 citation statements)
references
References 48 publications
7
163
0
Order By: Relevance
“…ATF4 is involved in ferroptosis in cancer cells (Chen, Fan et al, 2017; Chen, Wang et al, 2017). We next detected ATF4 expression in hepatoma cells exposed to erastin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ATF4 is involved in ferroptosis in cancer cells (Chen, Fan et al, 2017; Chen, Wang et al, 2017). We next detected ATF4 expression in hepatoma cells exposed to erastin.…”
Section: Resultsmentioning
confidence: 99%
“…In glioma cells, the silencing of ATF4 has been suggested as a solid strategy for impairing glioma growth and vasculature by sensitizing tumor cells to erastin‐ and RSL3‐induced ferroptosis (Chen, Fan et al, 2017). In breast cancer cells, knockdown of ATF4, on the contrary, prevented cystine starvation‐induced ferroptosis (Chen, Wang et al, 2017). Our present data demonstrated that miR‐214 suppressed ATF4 transcription and led to its protein reduction in HepG2 and Hep3B cells exposed to erastin.…”
Section: Discussionmentioning
confidence: 99%
“…The three related PanK genes encode pantothenate kinases, which are enzymes that control the ratelimiting step in CoA biosynthesis (21)(22)(23). CHAC1 (cation transport regulator homolog 1) encodes a stress-response protein that digests glutathione, regulating redox potential and enhancing ferroptosis (13,24). In addition to these p53 target genes, we examined the well-recognized ferroptosis biomarkers ALOX15 and ALOX12, which encode proteins that catalyze the peroxidation of polyunsaturated fatty acids to drive ferroptosis (11,25,26).…”
Section: Resultsmentioning
confidence: 99%
“…CHAC 1 is the downstream of ATF4 and demonstrated to promote the degradation of GSH and the subsequent ferroptosis ( Figure 1). 5,50 PUMA is another downstream of ATF4 and is also up-regulated during the ER stress induced by the ferroptotic reagents, artemisinins (ART). However, PUMA activation will induce apoptotic cell death under the treatment of ferroptotic agents.…”
Section: Er In Ferroptosismentioning
confidence: 99%